Pengembangan Perangkat Pembelajaran Tematik Berorientasi Pendekatan Saintifik Dalam Upaya Membangun Kecerdasan Siswa Di Kelas I Sekolah Dasar - Mayarnimar , (Prosiding Seminar Nasional Jurusan PGSD FIP UNP Tahun 2015, 2015)
This was a developmental research which was intended to develop valid, practical, and effective scientific approach-oriented thematic instructional materials in class I of Elementary School which involve Lesson Plan and learning materials. The instructional materials were developed by using 4-D model (Defining, Designing, Developing, and Disseminating). The disseminating phase, however, was done in a limited scale. The design was validated by three experts and three educational practitioners. To see the practicality and the effectiveness of the materials developed, it then was tried out limitedly to the students in class I of SD Negeri Percobaan Padang. Based on the result of the research, it was concluded that the scientific approach-oriented thematic instructional materials developed had been valid, practical, and effective.